Dynamic mechanical behavior and constitutive relationship of rubber fiber concrete after high temperature - Hengxiang Shen; Hongguang Ji; Xiang Peng; Zhuhua Tian; Guangning Su (Scientific Reports)
Abstract To investigate the effect of temperature on the dynamic mechanical properties of rubber–polypropylene fiber concrete (RPFC), dynamic mechanical parameters and energy parameters of RPFC at different temperatures were obtained using the Split Hopkinson Pressure Bar (SHPB) test. Subsequently, the particle size distribution and fractal dimension of RPFC were calculated through a standard square-hole sieving test, and the relationship between the energy dissipation per unit volume and the fractal dimension was analyzed. Finally, by introducing a temperature damage factor and a strain damage factor, a dynamic damage constitutive model of RPFC considering both temperature and strain damage was established. The results show that under the same impact pressure, the dynamic peak strength of RPFC first decreases and then increases with rising treatment temperature, with a maximum increase of 24.3% and a maximum decrease of 16.5%. The dynamic elastic modulus shows a decreasing trend, with a maximum reduction of up to 14.8%. Due to the anchoring effect of polypropylene fibers within the concrete matrix, the failure energy per unit volume first increases and then decreases. As the unit failure energy increases, the increment of the fractal dimension at 100 °C is greater than that at 25 °C. At 300 °C, the high-temperature melting of polypropylene fibers generates steam, which helps relieve internal pore pressure caused by high temperatures, thereby reducing internal damage in RPFC. The increase in fractal dimension under this condition is gradual and approximately linear. The fitting of the experimental stress–strain curves indicates that the dynamic constitutive model incorporating thermal and strain damage is applicable to rubber and polypropylene fiber-reinforced concrete.